2004
DOI: 10.1055/s-2004-822782
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaktische Splenektomie während Resektion bei chronischer Pankreatitis

Abstract: Complications of prophylactic splenectomy are rare and less frequent than reported episodes of variceal bleeding. In the presence of asymptomatic SVT splenectomy should be considered during pancreatic resection to facilitate surgery and to avoid further variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For example, between 1969 and 1984, 45% of patients reported with PISVT initially presented with GI bleeding 7 . Similarly, removing the limit on study age in the literature included in this analysis yields an overall PISVT incidence of 14.1% (22.6% in AP and 12.4% in CP) and a bleed rate of 19.0% 2,3,6,7,9,11–14,17–45 . A comparison of these data with results reported in the current review indicates both an increasing awareness of PISVT and a decreasing concern for GI bleed in the era of universal cross‐sectional imaging.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, between 1969 and 1984, 45% of patients reported with PISVT initially presented with GI bleeding 7 . Similarly, removing the limit on study age in the literature included in this analysis yields an overall PISVT incidence of 14.1% (22.6% in AP and 12.4% in CP) and a bleed rate of 19.0% 2,3,6,7,9,11–14,17–45 . A comparison of these data with results reported in the current review indicates both an increasing awareness of PISVT and a decreasing concern for GI bleed in the era of universal cross‐sectional imaging.…”
Section: Discussionmentioning
confidence: 58%
“…A meta‐analysis of contemporary studies meeting inclusion criteria showed an overall mean reported incidence of PISVT of 14.1% (Figure 5). 11,13,17,25–29,36 Mean incidences varied from 22.6% in patients with AP to 12.4% in patients with CP. The incidence of associated splenomegaly was only 51.9% 3,6,7,9,11,13,18,19,24,26,28,36,42,46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[292122] SAE can also be performed prior to splenectomy to decrease arterial flow into the left portal system. [42324] Splenectomy and SAE interrupt the arterial supply to the feeding collateral veins and thus decompressing gastric varices and consequently reduced risk of variceal re-bleeding. [31525]…”
Section: Discussionmentioning
confidence: 99%